La Neosofística y los Nuevos Sofismas - Padrón, José (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2000)
This essay argues that neo-sophism is used in social science language as a way to hidden weak arguments. If sophism was used in Antiquity, neo-sophism is the contemporary use of rhetorical arguments in order to present some ideas in the social sciences. It describes the structure of this kind of thought and highlights its main characteristics.